Pancreatic alkaline phosphatase and a tumour variant. Issue 7 (July 1972) - Warnes, T. W.; Timperley, W. R.; Hine, Pauline; Kay, G.
Abstract : Alkaline phosphatase has been extracted from human pancreas with n-butanol and has been shown to have distinctive isoenzyme characteristics when compared with the enzymes of small intestine and of normal serum. The enzyme has been demonstrated histochemically in a carcinoma of the pancreas and also in an islet cell tumour and the tumour enzyme has been shown to be unique, not only electrophoretically, but in being remarkably heat sensitive and in being activated by low molarities of urea.